Sustainable intensification of crop production: reviewing current knowledge and investigating opportunities for bread with lower global warming potential - Ryan, Luke Patrick (Kansas State University, 2023)
The move toward sustainable crop production has brought attention to environmental issues; meanwhile, the growing population pressures the food system to increase production. Sustainable intensification addresses both issues by intensifying management to increase production while still being environmentally sound; however, definitions and quantifications of sustainability have been inconsistent and subjective. Therefore, this thesis attempted to provide clarity about sustainable intensification of crop production following two major strategies: (i) a comprehensive literature review of current knowledge across major crops, and (ii) a field and laboratory study to inform decision making in bread wheat systems. In our first effort, we conducted a review of sustainability literature to identify commonalities in definitions, themes, and indicators across the production, environmental, economic, social, and human condition domains of sustainability. We also reviewed metrics and tools commonly used in sustainability studies, including those applicable to research and those relevant at the farm level. In addition, current sustainability literature representing four of the major food crops [wheat, Triticum aestivum L.; rice, Oryza sativa L.; maize, Zea mays L.; and soybeans, Glycine max (L.) Merrill] was investigated to identify common topics and research gaps. A majority of these studies addressed production and environmental or economic indicators of sustainability, with fewer studies delving into human or social aspects. Translation of research findings to field applications (i.e., the adoption of sustainable practices and technologies by producers) seem to be limited by adoption initial cost (not only direct monetary but also in terms of human capital) and unavailability. There seems to be opportunities for future research to include end-use quality parameters in sustainability assessments and to increase the robustness of small-scale assessments of social and human condition sustainability. In our second effort, we established field experiments where we replicated the management intensities currently adopted in commercial wheat fields to identify avenues to increase bread production and improve or maintain environmental footprints simultaneously. Four management intensities (i.e., low, average, high, and top) were derived from a survey of 656 commercial fields and replicated in trials conducted in 23 site-year combinations in the sub-humid and semi-arid regions of Kansas. Milling and baking analysis provided quality data to the loaf of bread. Cradle-to-grave life cycle assessment (LCA) quantified global warming potential (GWP) and energy inputs relative to a functional unit of 1 kg of bread, while estimates of carbon sequestration and bread energy output allowed the calculation of net GWP and net energy yield (NEY). As management intensity increased, both grain yield and protein increased despite a negative relationship between the two within management intensity. The combination of yield and protein gains resulted in higher bread yields. GWP and energy inputs for both the wheat production phase and the entire bread production system increased as a result of added inputs with each step of intensity, but the magnitude of increase when yield-scaled was alleviated by increases in bread yield. Although mean GWP and energy input increased with more intensive management (1.22-1.46 kg-CO₂e and 15.02-16.34 MJ per kg-bread⁻¹), differences decreased as bread yield increased, which was further reduced when net GWP and NEY were considered. These results suggest an opportunity to increase bread yields with minor increases in environmental impact per unit bread.
Keywords: Sustainable intensification; Life cycle assessment; Wheat bread; Global warming potential; Sustainability domains; Wheat production